Genome-wide association study for single nucleotide polymorphism associated with mural and cumulus granulosa cells of PCOS (polycystic ovary syndrome) and non-PCOS patients - Pankaj Pant; Havagiray Chitme; Reema Sircar; Ritu Prasad; Hari Om Prasad (SpringerOpen, 2023)
Highlights Investigated genetic make-up of mural and cumulus granulosa cells Role of these cells in pathogenesis of PCOS studied Local and systematic effect of these genes were correlated